High-Quality Library Preparation for NGS-Based Immunoglobulin Germline Gene Inference and Repertoire Expression Analysis - Vázquez Bernat, Néstor; Corcoran, Martin; Hardt, Uta; Kaduk, Mateusz; Phad, Ganesh E.; Martin, Marcel; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2019)
Next generation sequencing (NGS) of antibody (Ab) repertoires (Rep-seq) enables examination of the adaptive immune system at an unprecedented level. Applications include studies of expressed repertoires, gene usage, somatic hypermutation levels, Ab lineage tracing and identification of genetic variation within the immunoglobulin (Ig) loci through inference methods. All these applications require starting libraries that allow the generation of sequence data with low error rate and optimal representation of the expressed repertoire. Here, we provide detailed protocols for the production of libraries suitable for human Ig germline gene inference and Ab repertoire studies. Various parameters used in the process were tested in order to demonstrate factors that are critical to obtain high quality libraries. We demonstrate an improved 5’RACE technique that reduces the length constraints of Illumina MiSeq based Rep-seq analysis but allows for the acquisition of sequences upstream of Ab V genes, suitable for primer design. We then describe a 5’ multiplex method for library preparation, which yields full length V(D)J sequences suitable for genotype identification and novel gene inference. We provide comprehensive sets of primers targeting VH, VK and VL genes. Using the optimized protocol, we produced IgM, IgG, IgK and IgL libraries and analyzed them using the germline inference tool IgDiscover to identify expressed germline V alleles. This process additionally uncovered three VH, one VK and six VL novel alleles in a single individual, which are absent from the IMGT reference database, highlighting the need for further study of Ig genetic variation. The library generation protocols presented here enable a robust means of analyzing expressed Ab repertoires, identifying novel alleles and producing individualized germline gene databases from humans.